2004
DOI: 10.1021/cm048992l
|View full text |Cite
|
Sign up to set email alerts
|

Using Block Copolymer Micellar Thin Films as Templates for the Production of Catalysts for Carbon Nanotube Growth

Abstract: We report a novel approach that uses block copolymer micelles as a means to create large area arrays of iron-containing nanoclusters capable of catalyzing the growth of carbon nanotubes (CNTs). The amphiphilic block copolymer poly(styrene-block-acrylic acid) (PS-b-PAA) forms micelles in solution which are capable of self-organizing into ordered structures on surfaces. By spin-coating these solutions onto a variety of substrates, we can create quasihexagonal arrays of PAA spheres within a PS matrix. The carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 18 publications
1
65
0
Order By: Relevance
“…Preparation of Carbon Nanotube Growth Catalysts: Details about synthesizing iron oxide nanocluster arrays have been published previously [21,22,24]. In brief, PS-b-PAA was mixed with toluene at a concentration of 10 mg mL -1 and heated to 145°C for 20 min in a sealed vial to create a spherical block-copolymer micellar solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of Carbon Nanotube Growth Catalysts: Details about synthesizing iron oxide nanocluster arrays have been published previously [21,22,24]. In brief, PS-b-PAA was mixed with toluene at a concentration of 10 mg mL -1 and heated to 145°C for 20 min in a sealed vial to create a spherical block-copolymer micellar solution.…”
Section: Methodsmentioning
confidence: 99%
“…[21,22,24] The polymer thin film was then treated in oxygen plasma to remove the organic components, leaving an iron oxide nanocluster array, as shown in Figure 1A. Previous studies have demonstrated that the iron oxide nanocluster structure is Fe 2 O 3 .…”
mentioning
confidence: 99%
“…These periodic nanostructures can potentially be utilized as templates for creating metal nanostructures with controlled features, such as size or spacing. There are various reports describing the incorporation of inorganic functional components into microdomains of self-assembled block copolymer thin film structures or micelles [19,[23][24][25][26][27][28][29][30][31], proving it to be a promising tool for the preparation of nanostructured arrays with tunable spacing and size. Selective loading of BCP domains with metallic nanoparticles usually requires three conceptual steps: firstly, creating the BCP thin film or micelles on a substrate, secondly, impregnating selectively one domain of BCP with certain precursor, and, finally, formation of metal nanoparticles, which is sometimes followed by a separate step of BCP destruction.…”
Section: Introductionmentioning
confidence: 99%
“…A first well-known procedure for the production of metal NP arrays consists of using BCP micelles as reservoirs for the loading of metal salts, either in solution [18,19] or after the micellar film deposition [20][21][22]. Selective binding between metal salts and BCPs occurs via the formation of p complexes with olefin groups [23], electrostatic interactions [18,24] or metal coordination reactions [25] with a polar group, often nitrogen atoms of pyridine units.…”
Section: Introductionmentioning
confidence: 99%